Su alcune varianti redazionali del testimone fiorentino dell’Iwein di Hartmann von Aue - Maria Rita Digilio (Filologia Germanica)
ON SOME TEXTUAL VARIANTS OF THE FLORENCE MANUSCRIPT OF HARTMANN VON AUE’S ‘IWEIN’. An important witness of Hartmann von Aue’s Iwein is preserved in the Biblioteca Nazionale in Florence (pressmark: B. R. 226). This manuscript (which also contains Gottfried von Straßburg’s Tristan and its continuation by Heinrich von Freiberg), has been dated to the first half of the 14th century and seems to be of Bohemian provenance. The text of the Iwein shows peculiar and often exclusive textual variants, as compared to the other witnesses of Hartmann’s masterwork. Its main feature is a considerable simplification of syntactical constructions, which often entails a certain banality in the description of the characters’ psychological traits and of the events, as well as the loss of peculiar literary narrative strategies, resulting in an apparent decrease of the poetic quality of the romance. It is noteworthy that the Florence Iwein shares most of these features with the late courtly romances, so that a late remodelling of Hartmann’s original text may be conjectured. Moreover, from a number of syntactical and prosodic strategies it may be inferred that the Florence Iwein preserves some echoes of an oral performance of the text. Finally, it should be noted that at least two important thematic focuses of Hartmann’s work (concerning Iwein’s relationship to the lion and to his wife Laudine) are stressed in a peculiar way in the Florence witness, where they receive a much clearer exemplification than in the presumably original version of the romance.